COPZ1 depletion in thyroid tumor cells triggers type I IFN response and immunogenic cell death. (28th April 2020) - Di Marco, Tiziana; Bianchi, Francesca; Sfondrini, Lucia; Todoerti, Katia; Bongarzone, Italia; Maffioli, Elisa Margherita; Tedeschi, Gabriella; Mazzoni, Mara; Pagliardini, Sonia; Pellegrini, Sandra; Neri, Antonino; Anania, Maria Chiara; et al.
Abstract: The coatomer protein complex zeta 1 (COPZ1) represents a non-oncogene addiction for thyroid cancer (TC); its depletion impairs the viability of thyroid tumor cells, leads to abortive autophagy, ER stress, UPR and apoptosis, and reduces tumor growth of TC xenograft models. In this study we investigated the molecular pathways activated by COPZ1 depletion and the paracrine effects on cellular microenvironment and immune response. By comprehensive and target approaches we demonstrated that COPZ1 depletion in TPC-1 and 8505C thyroid tumor cell lines activates type I IFN pathway and viral mimicry responses. The secretome from COPZ1-depleted cells was enriched for several inflammatory molecules and damage-associated molecular patterns (DAMPs). Moreover, we found that dendritic cells, exposed to these secretomes, expressed high levels of differentiation and maturation markers, and stimulated the proliferation of naïve T cells. Interestingly, T cells stimulated with COPZ1-depleted cells showed increased cytotoxic activity against parental tumor cells. Collectively, our findings support the notion that targeting COPZ1 may represent a promising therapeutic approach for TC, considering its specificity for cancer cells, the lack of effect on normal cells, and the capacity to prompt an anti-tumor immune response. Highlights: COPZ1 represents a non-oncogene addiction for thyroid cancer. COPZ1 silencing stimulates type I IFN response and inflammation. COPZ1 silencing induces immunogenic cell death, dendritic and T cell activation. COPZ1 depletion prompts an anti-tumor immune response. COPZ1 targeting represents a new therapeutic strategy for advanced thyroid cancer.